Qualitative analysis of chemical components in Lianhua Qingwen capsule by HPLC-Q Exactive-Orbitrap-MS coupled with GC-MS - Shuai Fu; Rongrong Cheng; Zixin Deng; Tiangang Liu (Elsevier, 2021)
The Lianhua Qingwen (LHQW) capsule is a popular traditional Chinese medicine for the treatment of viral respiratory diseases. In particular, it has been recently prescribed to treat infections caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). However, due to its complex composition, little attention has been directed toward the analysis of chemical constituents present in the LHQW capsule. This study presents a reliable and comprehensive approach to characterizing the chemical constituents present in LHQW by high-performance liquid chromatography-Q Exactive-Orbitrap mass spectrometry (HPLC-Q Exactive-Orbitrap-MS) coupled with gas chromatography-mass spectrometry (GC-MS). An automated library alignment method with a high mass accuracy (within 5 ppm) was used for the rapid identification of compounds. A total of 104 compounds, consisting of alkaloids, flavonoids, phenols, phenolic acids, phenylpropanoids, quinones, terpenoids, and other phytochemicals, were successfully characterized. In addition, the fragmentation pathways and characteristic fragments of some representative compounds were elucidated. GC-MS analysis was conducted to characterize the volatile compounds present in LHQW. In total, 17 compounds were putatively characterized by comparing the acquired data with that from the NIST library. The major constituent was menthol, and all the other compounds were terpenoids. This is the first comprehensive report on the identification of the major chemical constituents present in the LHQW capsule by HPLC-Q Exactive-Orbitrap-MS, coupled with GC-MS, and the results of this study can be used for the quality control and standardization of LHQW capsules.